Public sector financial management - Coombs, Hugh Malcolm; Jenkins, D. E. (London : International Thomson Business Press, 1997)
Introduction. Operational and service-based costing. Cost variability and relevant costs. Budgeting. Budgetary control. The management of working capital. The financing of capital expenditure. Capital budgets and capital programmes. Project appraisal. The audit of public sector organizations.
Keywords: Finance; Managerial accounting; Managerial accounting; Finance, Public